Раскопки пещерного храма 2 у мыса Виноградный на Гераклейском полуострове - Яшаева, Т.Ю. (Археологічні дослідження в Україні, 2010)
In 2009, the Byzantine Expedition of the National Preserve Tauric Chersonesos headed by T.Yu. Yashayeva studied not known before Christian mediaeval Cave Temple 2 in the vicinity of Chersonesos near Vynohradnyi Cape. The temple got through two construction periods and was destroyed by the fire in the Late Byzantine period.